Influence of the Internal Marketing Communication On The Work Performance - Jakub MICHULEK; Anna KRIZANOVA (Communications of International Proceedings, 2022)
Nowadays, companies realize the importance of satisfied and informed employees. If the employee feels like a part of the company and his requirements are met, the result is a low level of fluctuation. This can be reached through internal marketing communication. Internal marketing communication is not a philosophy focused only to the last few years. It is a concept, that can ensure the success of the company because if employees understand and are identified with the company’s goals and vision, they will do their work effectively. Thanks to this, can the company achieve its goals, achieved concurrence advantage, and satisfy customers’ needs. The primary aim of this research was to identify if internal marketing communication has an influence on the work performance of the company’s employees. The data was obtained through a questionnaire. The data were evaluated by using MS Excel and IBM SPSS Statistic. We used Pearson's χ2 test to evaluate the data to see if there was a dependency between the variables or not. We used Spearman's Rho to find out what the addiction was. According to the performed analysis of the data, we found, based on Pearson's χ2 test, that there is a dependence between the examined variables of the level of internal marketing communication and the level of employee performance. This is a moderate dependence, which we revealed through the use of Spearman’s correlation, Rho.
Keywords: Communication; Internal Marketing Communication; Internal Marketing; Work Performance